ダイ10ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク 1968 1969 - 村越, 望; ムラコシ, ノゾミ; MURAKOSHI, Nozomi (国立極地研究所, 1969)
P(論文) Forty members of the 10th Japanese Antarctic Research Expedition left Tokyo on November 30, 1968, aboard the icebreaker FUJI, under the command of Captain Shigeo MATSUSHIMA The expedition was led by Dr Kou KUSUNOKI, also leading the wintering party of 28 men and one pressman, while the author, as deputy leader, led the summer party of 12 men and one press reporter At Fremantle, West Australia, an american scientist (aeronomy) Mr Gerard A ROACH got on board the FUJI as an observer The FUJI carried 560 tons of expedition's cargo, including a single-engine monoplane Lockheed LASA-60, and was equipped with two Sikorsky S61-A helicopters and one Bell 47G2A helicopter After anchoring at Fremantle from December 15 through 21, 1968, the FUJI proceeded to Lutzow-Holm Bay and reached the edge of fast ice on January 5, 1969, without much difficulty The anchorage was about 30 nautical miles northeast of Syowa Station, and from there the first helicopter flight was made to transport men and cargo. On the following day, January 6, the FUJI reached fast ice within 1400 meters east of Syowa Station Unloading of about 560 tons of cargo and transportation to the station were carried out mainly by two S61-A helicopters, but about 65 tons of diesel oil was transmitted by a pipeline directly from the ship to the tanks on the shore, one 50kl metal tank and three 10kl rubber pillow tanks This was the first attempt of oil transportation by a pipeline. The remaining 105 tons of heavy materials were transported by snow vehicles and sledges over sea ice. Construction works was carried out until February 20, and a new living hut (20 × 5m), an extention of garage (10 × 8m), a tidal observation hut (3 × 3m), a corridor and three rocket huts, an assembly shop (11.8 × 7.6m), a telemetry and rador station (14.9 × 6.5m), and a control center (6.0 × 3.6m) were completed For the constructions, we were provided with a new 11-ton bulldozer, a 2-ton dump truck, and a concreat mixer. The scientific activities were largely the continuation from ...